Mary Shelley in her times - Bennett, Betty T.; Curran, Stuart (Johns Hopkins University Press, 2000)
"This collection of essays offers a more complete and complex picture of Mary Shelley, emphasizing the full range and significance of her writings in terms of her own era and ours. Mary Shelley in Her Times brings fresh insight to the life and work of an often neglected or misunderstood writer who, the editors remind us, spent nearly three decades at the center of England's literary world during the country's profound transition between the Romantic and Victorian eras."--Jacket